Terahertz Absorption Properties of Two Solid Amino Acids and Their Aqueous Solutions - Ye, Ping; Wang, Guoyang; Yang, Yizhou; Meng, Qinghao; Wang, Jiahui; Su, Bo; Zhang, Cunlin (International Journal of Optics, 2021)
A new type of embedded cyclic olefin copolymer microfluidic chip was designed and combined with terahertz (THz) technology to study the effects of glycine and arginine on the THz wave absorption characteristics. This study aims to understand the interactions between solid amino acid molecules and between amino acid and water molecules and to determine the changes in their microstructure. By observing the intensity of the time domain spectra in the range of 0.2–2.6 THz, we found that, as the concentration of glycine and arginine increased, the THz transmission gradually decreased. It can be inferred that the molecular structure and quantity of different amino acids have different influence on the hydrogen bond, which affects the absorption coefficient in solution. It was also found that the terahertz technique is able to identify the solid amino acid species better, and it can also perform some species identification for liquid amino acids. These results provide a reference for future studies on the terahertz absorption properties of amino acid samples. Moreover, Gaussian16 software was used to calculate the terahertz spectra using the density functional theory, B3LYP functional, and 6-31G basis set. Additionally, Gaussian View6 video software provided the frequency values, molecular vibration modes of the theoretical absorption peaks of glycine, arginine, and its aqueous solutions in the frequency range of 0.2–2.6 THz, which offers theoretical support for future studies.